Ambisonics : a practical 3D audio theory for recording, studio production, sound reinforcement, and virtual reality /: a practical 3D audio theory for recording, studio production, sound reinforcement, and virtual reality. ([2019]) - Zotter, Franz; Frank, Matthias
No abstract available